Radon-Distribution Measurements With CR-39, LR-115 And CN-85 DeteCtors - Mahdi, K. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The  aim  of this  work  is to determine radon and  its decay  product concentratiQns  indoor   and  outdoor   in  different   areas   in  north   and middle  areÂ·a of Iraq by using nuclear  trak detectors  , CR-39  , CN- 85 andLR-115.                        -For   CR-39    detectors   ,   the   highest    radon    concentration  was(64.07Bq/m3)indoor and  (52.4  Bq/m3)outdoor  , in Autumn  season  .And the concentration of that radon and its decay product  indoor  were greater  than outdoor  . temperature seems  to  playsapredominant role in the formation of radon concentration .